Young people and sexual risk-taking behaviour in Central England - Westwood, J.; Mullan, Barbara (C S I R O Publishing, 2009)
Background: Sexually transmissible infections and the rate of teenage pregnancy in the UK are among the highest in the industrialised world. Research has suggested that high rates of risk-taking behaviours may account for the concerning increase in the rates of sexually transmissible infections and higher rates of teenage pregnancy in the UK. Methods: This cross-sectional analysis investigated the sexual risk-taking behaviours of a group of sexually active 12–15-year-old school pupils from a single county in Central England (n = 493). Data were analysed to investigate the sexual risk activity of adolescents, urban/rural location, and gender. Results: In this sample, rural students were more likely than their urban counterparts to have used drugs or alcohol the first time they had sex. Female students were more likely than male students to report ever having had sex without contraception. Male students were more likely than female students to have ever had a one night stand. Conclusions: As expected there were differences in sexual risk-taking behaviour between pupils in urban and rural locations, and males and females. In most cases these differences were consistent with previous research on general trends, with a few exceptions that can be meaningfully interpreted using previous research in this area. In future, researchers may wish to investigate the underlying factors that determine these differences in risk-taking behaviour.